At the threshold of symbiosis: the genome of obligately endosymbiotic 'Candidatus Nebulobacter yamunensis' is almost indistinguishable from that of a cultivable strain. Issue 12 (14th December 2022) - Giannotti, Daniele; Boscaro, Vittorio; Husnik, Filip; Vannini, Claudia; Keeling, Patrick J.
Abstract : Comparing obligate endosymbionts with their free-living relatives is a powerful approach to investigate the evolution of symbioses, and it has led to the identification of several genomic traits consistently associated with the establishment of symbiosis. ' Candidatus Nebulobacter yamunensis' is an obligate bacterial endosymbiont of the ciliate Euplotes that seemingly depends on its host for survival. A subsequently characterized bacterial strain with an identical 16S rRNA gene sequence, named Fastidiosibacter lacustris, can instead be maintained in pure culture. We analysed the genomes of ' Candidatus Nebulobacter' and Fastidiosibacter seeking to identify key differences between their functional traits and genomic structure that might shed light on a recent transition to obligate endosymbiosis. Surprisingly, we found almost no such differences: the two genomes share a high level of sequence identity, the same overall structure, and largely overlapping sets of genes. The similarities between the genomes of the two strains are at odds with their different ecological niches, confirmed here with a parallel growth experiment. Although other pairs of closely related symbiotic/free-living bacteria have been compared in the past, ' Candidatus Nebulobacter' and Fastidiosibacter represent an extreme example proving that a small number of (unknown) factors might play a pivotal role in the earliest stages of obligate endosymbiosis establishment.